PARENTING PATTERNS OF CORRECTIONAL OFFICERS TO OVERCOME ANXIETY OF FOSTER CHILDREN IN LPKA CLASS I TANGERANG - Zaynudin, Alan; Hamzah, Imaduddin (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Children who get a criminal verdict and carry out sentences in LPKA will get various problems and cause anxiety in the process of interacting with individuals and groups of fostered children and officers. The anxiety felt by children in LPKA is due to the limitations and freedoms that are restricted and require time to adapt to their new environment. The condition of foster children whose space is limited has an impact on their psychology, which can cause anxiety. Children are sentenced to punishment not without cause but for the actions they have committed so that they serve their sentence in LPKA. The correctional officers, by using the parenting approach, will help foster children to accept the conditions that are being experienced and provide motivation for foster children to still have a spirit of life and try to improve themselves. Officers can play a role like parents to provide parenting to foster children through coaching and education undertaken by children while in LPKA, which will be able to affect the mental and psychological condition of children. Keywords: Anxiety; Child; Correctional Officer